Zur Frage der Geometrie der homogenen Räume - Vosylius, R. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. В. Восилюс. К геометрии однородных пространств R. Vosylius. Homogeninių erdvių geometrijos klausimu